Security and Justice in Isaiah - Roberts, Jimmy J. M. (Stone-Campbell journal, 2010)
Isaiah of Jerusalem maintained a consistent opposition to Judah's various attempts to achieve national security through international military alliances. Instead, he urged Judah's leaders to trust in the promises Yahweh had made to the Davidic dynasty and to Jerusalem, God's royal city. According to Isaiah, if the rulers made God the object of their fear and obeyed him by providing justice and relief to the poor of God's people, the result would be peace and prosperity for the whole nation.